Enhancing overall properties of epoxy-based composites using polydopamine-coated edge-carboxylated graphene prepared via one-step high-pressure ball milling. Issue 39 (2nd August 2019) - Ren, Shujie; Meng, Liu; Ma, Wenli; Lin, Song; Yang, Wengang; Lan, Jinle; Jia, Xiaolong; Cai, Qing; Yang, Xiaoping
Abstract : Overall properties of epoxy-based composites were enhanced by using polydopamine-coated edge-carboxylated graphene prepared via one-step high-pressure ball milling. Abstract : Graphene (GN) nanofillers have been widely used to enhance the overall performance of polymer composites due to their various superior properties, which strongly rely on the uniform dispersion and strong interfacial bonding of GN with high-quality polymer matrices. In the present study, the strengthening and functional effects of polydopamine-coated edge-carboxylated graphene (p-ECG) on the mechanical, moisture-barrier and electromagnetic properties of epoxy (EP)-based composites were systematically evaluated. p-ECG was successfully prepared via one-step high-pressure ball milling through the edge-selective functionalization and exfoliation of pristine graphite in the presence of dry ice, followed by synchronous reduction and coating via the mild oxidative polymerization of mussel-inspired dopamine. p-ECG showed prominent advantages of a small sheet size, excellent dispersibility and high chemical reactivity in the EP matrix. Obvious enhancements were achieved in the tensile and flexural properties and moisture-barrier performance of EP composites as well as the interlaminar shear strength (ILSS) and transverse fiber bundle tensile (TFBT) strength of carbon fiber (CF)/EP composites, which confirmed the excellent dispersion and chemically strengthened interfacial bonding of p-ECG in the EP matrix. More importantly, p-ECG introduced onto the surface of desized CF led to significant enhancement in the electromagnetic interference (EMI) shielding capability of CF/EP composites, which was primarily ascribed to the polarization relaxation effect induced by the defects and functional groups in p-ECG as well as the increase in electrical conductivity derived from the "bridging effect" of p-ECG. Specifically, with p-ECG content of 0.5 wt%, the increments in tensile strength, TFBT strength, shielding effectiveness (total, SET ) and shielding effectiveness (reflection loss, SER ) were as high as 33.3, 34.3, 31.3 and 71.0%, respectively.